Assessment of Depression and Quality of Life among Elderly in a Rural Area of Goa, India - Jennifer Mendes; Hemangini K Shah (Indian Journal of Social Psychiatry)
Background: By 2025, disability-adjusted life years attributable to depression are projected to rise by about 2.6 million (22.5%) due to population growth and aging. Assessing depression and analyzing the quality of life (QoL) among this vulnerable population are vital so that necessary measures to promote healthy aging can be implemented at the community level. Hence, our study was proposed to estimate the prevalence of depression and assess associated factors and QoL among the rural elderly population. Materials and Methods: A cross-sectional study was conducted among the elderly population of a rural area in Goa, India, over 1 year. Data were collected using a semi-structured questionnaire, including sociodemographic details, lifestyle factors, and medical history. Depression and QoL were assessed using the Geriatric Depression Scale-15 and short form-12 scale, respectively. Data were analyzed using SPSS version 22. Results: The total number of participants enrolled in the study was 384, of which majority, 60.2%, were in the age group of 60–69 years. The prevalence of depression in the current study was 29.2%. There was a statistically significant association between depression and the following variables: sex, self-reported insomnia, marital status, presence of major stressors, living arrangement, and physical activity. Among the study participants, 35.2% and 21.6% had low (<50) physical component summary and mental component summary scores, respectively. The association of depression and QoL was found to be statistically significant. Conclusion: Recognizing depressive symptoms among the elderly at an early stage is crucial for managing depression and providing timely remedial measures to improve their QoL.